2009
DOI: 10.1016/j.immuni.2008.12.019
|View full text |Cite
|
Sign up to set email alerts
|

A Role for cis Interaction between the Inhibitory Ly49A Receptor and MHC Class I for Natural Killer Cell Education

Abstract: Natural killer (NK) cells show enhanced functional competence when they express inhibitory receptors specific for inherited major histocompatibility complex class I (MHC-I) molecules. Current models imply that NK cell education requires an interaction of inhibitory receptors with MHC-I expressed on other cells. However, the inhibitory Ly49A receptor can also bind MHC-I ligand on the NK cell itself (in cis). Here we describe a Ly49A variant, which can engage MHC-I expressed on other cells but not in cis. Even t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
132
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 42 publications
14
132
2
Order By: Relevance
“…This unexpected finding indicates that several mechanisms may control repertoire formation in response to MHC class I. It has been proposed that interactions between MHC class I and Ly49 receptors can occur in trans (between NK cells and other cells) as well as in cis (in the NK cell membrane itself) (32,33). One possibility is that the general shift in the repertoire toward few receptors results from MHC interactions in trans by the educating environment.…”
Section: Discussionmentioning
confidence: 99%
“…This unexpected finding indicates that several mechanisms may control repertoire formation in response to MHC class I. It has been proposed that interactions between MHC class I and Ly49 receptors can occur in trans (between NK cells and other cells) as well as in cis (in the NK cell membrane itself) (32,33). One possibility is that the general shift in the repertoire toward few receptors results from MHC interactions in trans by the educating environment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the murine system the interactions of Ly49A and MHC-I occur with identical specificity in both cis and trans, implying that the region of Ly49A that makes contact is the same in either case. Moreover, Ly49 constructs with shortened stalks appear able to function only in trans, suggesting the extension by the stalk is required to reach the MHC-I in cis, and that the cis and trans interactions are mediated by two distinct conformations of the receptor [30]. The long extracellular stalk region provides Ly49A with the flexibility necessary to mediate interactions with MHC-I in cis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory receptors bound in cis could potentially serve as a rheostat-like control mechanism to regulate the inhibitory input received by an NK cell in order to optimize activation efficiency. In mice it was reported that antibody-mediated sequestration of Ly49A, which mimics receptor sequestration by MHC-I in cis, can enhance the function of mature NK cells triggered via activating receptors [30]. During NK-cell development, a rheostat model has been proposed, where the inhibitory input an NK cell receives during education directly adjusts the efficiency of activation pathways in signaling responses [34,35].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since in our system cytokine stimulation can confer competence in the absence of any accessory cells, KIR could engage the cognate MHC molecule expressed on the same NK cell (cis interaction) or on neighboring NK cells (trans interaction). In mice it has been recently shown that cis interaction between inhibitory Ly49A receptor and MHC class I plays a role for education of NK cells [15]. Although the hypothesis that human NK-cell education as well is mediated via cis interaction would be very attractive, there is currently no evidence that the function of KIR is influenced by HLA expression in cis [16].…”
Section: Discussionmentioning
confidence: 99%